Family labor participation and child care decisions: The role of grannies - Gema Zamarro (SERIEs - Journal of the Spanish Economic Association, 2020)
Grandparents, and in particular grandmothers, are an important source of informal child care for their grandchildren in most developed countries. The literature shows how these informal transfers of care can help promote female labor participation. However, less is known about how working-age grandmothers are combining care with their own labor participation. In this paper, I use data from the Survey of Health, Aging and Retirement in Europe and analyze to what extent child care is provided by grandmothers in ten European countries and how grandmothers are combining this task with paid work. I also revisit the question of whether the child care provided by grandmothers is encouraging the labor participation of their offspring. The empirical approach takes into account the simultaneity of labor market decisions and caregiving activities while controlling for grandmother's unobserved heterogeneity on their willingness to provide care to their grandchildren. I find a negative and significant effect of participating in the labor market on the probability of taking care of the grandchildren on a regular basis. I also find evidence that, for some countries, the child care provided by working-age grandmothers has a positive effect on the labor participation of their daughters.
Keywords: J13; J21; C30; 330; Female labor participation; Child care decisions; Simultaneous estimation; Panel data